The quagga mussel, Dreissena rostriformis: a novel model for EcoEvoDevo, environmental research, and the applied sciences - Andreas Wanninger; Gudrun Schwarze (Frontiers in Cell and Developmental Biology)
Bivalve mollusks are globally distributed in marine and freshwater habitats. While exhibiting a relatively uniform bodyplan that is characterized by their eponymous bivalved shell that houses the soft-bodied animal, many lineages have acquired unique morphological, physiological, and molecular innovations that account for their high adaptability to the various properties of aquatic environments such as salinity, flow conditions, or substrate composition. This renders them ideal candidates for studies into the evolutionary trajectories that have resulted in their diversity, but also makes them important players for research concerned with climate change-induced warming and acidification of aquatic habitats. Some species, such as the blue and Mediterranean as well as the zebra and quagga mussels, form biodegradable fibers, the byssus threads. These have significant potential for biomimetic approaches by aiding in developing sustainable textiles and other fiber-based fabrics. Despite this broad span of scientific relevance, bivalves remain dramatically understudied and key resources such as high-quality genomes and developmental transcriptomes in combination with established laboratory protocols to carry out state-of-the-art molecular and morphological studies are only available for less than a handful of species. Here, we report on one of the best-investigated bivalves in this respect, the quagga mussel, Dreissena rostriformis, an invasive freshwater species. We summarize the current state of knowledge and available resources that make the quagga mussel highly amenable for studying adaptive mechanisms for life in hypoosmotic environments, biomineralization, biomimetics, and evolutionary developmental biology. We argue that the unique combination of biological features and the broad relevance of the quagga mussel for the basic and the applied sciences as well as for biomonitoring and conservation biology measures call for intensified research efforts using Dreissena rostriformis as a model.